2014
DOI: 10.1107/s1399004714007664
|View full text |Cite
|
Sign up to set email alerts
|

 L-allo-Threonine aldolase with an H128Y/S292R mutation fromAeromonas jandaeiDK-39 reveals the structural basis of changes in substrate stereoselectivity

Abstract: L-allo-Threonine aldolase (LATA), a pyridoxal-5'-phosphate-dependent enzyme from Aeromonas jandaei DK-39, stereospecifically catalyzes the reversible interconversion of L-allo-threonine to glycine and acetaldehyde. Here, the crystal structures of LATA and its mutant LATA_H128Y/S292R were determined at 2.59 and 2.50 Å resolution, respectively. Their structures implied that conformational changes in the loop consisting of residues Ala123-Pro131, where His128 moved 4.2 Å outwards from the active site on mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…Another investigation on the role of His128 was done for l - allo -TA A . jandaei ajTA (corresponding to His125 in tmTA and His126 in ecTA) by Tanokura (Qin et al 2014 ). In order to find the residues which are important for the catalytic activity, a mutant library was created by random mutagenesis and 3000 clones were screened for increased activity towards the cleavage of l - allo -threonine and l -threonine.…”
Section: Structure Catalytic Mechanism and Mutagenesis Studiesmentioning
confidence: 99%
“…Another investigation on the role of His128 was done for l - allo -TA A . jandaei ajTA (corresponding to His125 in tmTA and His126 in ecTA) by Tanokura (Qin et al 2014 ). In order to find the residues which are important for the catalytic activity, a mutant library was created by random mutagenesis and 3000 clones were screened for increased activity towards the cleavage of l - allo -threonine and l -threonine.…”
Section: Structure Catalytic Mechanism and Mutagenesis Studiesmentioning
confidence: 99%
“…It was postulated that the activated water molecule in the close position to C α acts as a base to abstract the C α proton and initiates the aldol reaction. The other residues, which participate in the protonation of the hydroxyl group of the product, were postulated to be His128 and His85 and are conserved among LTAs (Qin et al 2014;di Salvo et al 2014). A structural alignment using the Pymol program showed that the overall structure of LTA_Aj (accept glycine, alanine, and serine as donor) is highly similar to the previously reported LTA_Tm (Kielkopf and Burley 2002) with 49 % sequence identity and LTA_Ec (di Salvo et al 2014) with 54 % sequence identity (LTA_Tm and LTA_Ec accept only glycine as donor).…”
Section: Discussionmentioning
confidence: 57%
“…2c). As shown recently, the carboxylate group of an amino acid donor interacts with Arg171, Arg313, and Ser8 side chains that anchor the donor to the active site (Qin et al 2014). The donor ligand should be bound in the active site in the orientation that the scissile C α -H bond is oriented perpendicular to the plane of the PLP-donor ring (Toney 2005).…”
Section: Discussionmentioning
confidence: 85%
“…The conserved R313 in LTAaj acts as a α‐carboxylate docking site for the amino acid substrates . Similar to other Fold Type I PLP‐dependent enzymes, the electrostatic interaction between the carboxylic group of the α‐amino acid substrate and R313 in LTAaj may stabilize the Michaelis complex and maintain pKa of the C α atom .…”
Section: Resultsmentioning
confidence: 95%
“…The disruption of hydrogen bonding with N1 of PLP is not lethal for the aldol reactions catalysed by LTAaj, however significantly reduces the rates of a catalytic conversion. The conserved R313 in LTAaj acts as a a-carboxylate docking site for the amino acid substrates [29,30]. Similar to other Fold Type I PLP-dependent enzymes, the electrostatic interaction between the carboxylic group of the a-amino acid substrate and R313 in LTAaj may stabilize the Michaelis complex and maintain pKa of the C a atom [31].…”
Section: Resultsmentioning
confidence: 96%